Burkina Faso : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2004)
Performance under the program has been satisfactory. Real GDP growth is higher than estimated owing to substantially higher than projected agricultural production. Burkina Faso continues to depend heavily on external assistance and on cotton exports, and is highly vulnerable to terms-of-trade fluctuations and the volatility of aid flows. The government's continued resolve to strengthen transparency in public finance management, promote good governance, and combat corruption has been commended. The poverty reduction strategy program should take account of the revised macroeconomic framework.